2017
DOI: 10.4322/2526-8910.ctoao0934
|View full text |Cite
|
Sign up to set email alerts
|

As Contribuições Da Gameterapia No Desempenho Motor De Indivíduo Com Paralisia Cerebral

Abstract: The contributions of game therapy concerning motor performance of individual with cerebral palsyAbstract: Objective: In this study, it was analyzed the use of the videogame console Nintendo Wii™ as a motor (re) habilitation tool for individuals with Cerebral Palsy. Method: This is a field study with an exploratory and quantitative nature, in which is presented a case study. The participant's motor skills were assessed and reassessed using the standardized protocol GMFM-88 (Gross Motor Function Measure -88). It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 7 publications
0
3
0
9
Order By: Relevance
“…Overall, these studies showed the types of assessments being used to measure specific domains (DIAS et al, 2017). However, there remains a lack of evidence on what assessments are currently being used to measure outcomes specifically for OT interventions for children with CP.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, these studies showed the types of assessments being used to measure specific domains (DIAS et al, 2017). However, there remains a lack of evidence on what assessments are currently being used to measure outcomes specifically for OT interventions for children with CP.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that when working with children with disabilities, the use of playful tools increases interest and motivation to perform rehabilitation activities through games (REID, 2002), and virtual environments can contribute to therapeutic or rehabilitation intervention, and the evaluation process of these individuals (STANDEN; BROWN, 2005;DIAS et al, 2017). Children with Down syndrome are in this group of children with disabilities, in which the occupational therapist can increase their participation by adapting resources and strategies that provide opportunities for experimentation, learning, and interaction during games and playing (PELOSI, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Neste sentido, o console de videogame Nintendo  Wii (NW) se enquadra na abordagem da RV e tem sido usado na reabilitação de pacientes com desordens neurológicas, tais como a paralisia cerebral (PC), para a melhora de habilidades cognitivas e motoras (ANGUERA et al, 2013;DIAS et al, 2017;DE GR ANDE;GALVÃO;GONDIM, 2011;MOREIRA, 2012). Estudos mostram que a interação do sujeito com este recurso permite a execução de movimentos utilizados no desempenho das atividades de vida diária, estimulando, assim, a funcionalidade cotidiana (MOREIRA, 2012;CAIANA;NOGUEIRA;LIMA, 2016).…”
Section: Introductionunclassified
“…Neste estudo, conforme descrito por Dias et al (2017), a utilização de vídeo games como recursos terapêuticos integra o método de "gameterapia", o qual tem o potencial de viabilizar o processo de estimulação motora e/ou cognitiva. Especificamente, esse método pode viabilizar melhorias em habilidades perceptuais, atenção seletiva, concentração, pensamento abstrato, memória, organização viso-espacial, criatividade, funções executivas, entre outras habilidades cognitivas, por meio do aprendizado de habilidades e aquisição de conhecimento no contexto do jogo, o que facilita o aprendizado de novas tarefas em outros contextos (GREEN;BAVELIER, 2015;GRIFFITHS;KUSS;GORTARI, 2017).…”
Section: Introductionunclassified
See 1 more Smart Citation